Protection of Children in Child Learning During the Covid-19 Pandemic Indonesia - Meydora Cahya Nugrahenti; Hindina Maulida (Faculty of Law, Musamus University, 2021)
The Covid-19 pandemic has changed the implementation of face-to-face learning in schools (offline) to online. These changes make children unable to learn optimally due to various obstacles. This condition also affects the development and psychology of children. Data shows that the number of violence against children since the Covid-19 pandemic has tended to increase. On the other hand, children have the right to get protection and to grow properly in the context of education. The purpose of this study was to determine legal protection for children by analyzing legal provisions in Indonesia in protecting children's rights in online learning systems. The research method used is juridical normative with data sources obtained from primary, secondary, and tertiary sources. The data that has been collected is then presented in a structured and logical manner and analyzed descriptively. The results of the study found that legal protection instruments for children's rights in online learning systems already exist but their implementation has not been optimal. Socialization to prioritize children's growth and development rights in providing children's education rights during the Covid-19 pandemic must be more actively voiced to all Education Offices, heads of education units, educators, students, and parents of students.